I04 The effect of staged versus rapid immersion on the cardio-respiratory components of the cold-shock response - Brown, Joshua; Eglin, Clare (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Drowning is one of the leading causes of accidental death. Sudden cold-water immersion (CWI) leads to the stimulation of cutaneous cold receptors causing the cold-shock response (CSR) which includes a gasp, hyperventilation, and tachycardia for several minutes. Only one study has investigated staged CWI (Hayward and French, 1989, Av Space Env Med, 60, 1163-1165) and found a reduction in minute ventilation (V̇E) and respiratory frequency (fB) occurred when immersed to the waist for 30 s followed by to the shoulders. However, it is unclear whether a staged entry with a longer or shorter period at the waist would elicit a greater or lesser CSR. Thus, the aim of this study is to establish whether a staged immersion with a longer period immersed to the waist would attenuate the initial cardio-respiratory responses associated with CWI, when compared with rapid immersion. Ethical approval was gained from the University of Portsmouth Science Faculty Research Ethics Committee (SHFEC 2020-070). Seven male participants completed two, 5 min immersions that occurred at the same time of day (± 2 h) to avoid circadian variation in internal body temperature: a staged immersion (immersion to the iliac crest for 2 min prior to immersion to the acromion process); a rapid immersion (immersion to the acromion process for 5 min). Participants were lowered into stirred water (15°C) at a rate of 4 s to the waist, 4 s to the shoulder. Inspiratory and expiratory data were collected using a ventilatory turbine module and Douglas bags, respectively, whilst heart rate data was collected using a three-lead ECG. Variables were analysed over the first 30 s of immersion by a one-way ANOVA and a Tukey post hoc test. Effect sizes were calculated using Cohen’s d. Staged immersion to the waist resulted in a significantly lower fB (P < 0.05; d = 1.54) and V ̇E (P < 0.01; d = 1.96) over the first 30 s epoch, when compared to rapid immersion. Staged immersion to the shoulders resulted in a lower ventilatory equivalent of oxygen (P < 0.005; d = 1.95). There was no difference in heart rate between immersions. A staged immersion to the waist resulted in a 36.2% lower V̇E and 29.4% lower fB, potentially due to fewer cutaneous cold receptors being stimulated. This reduces the potential to aspirate water due to a lower ventilatory drive, therefore, could reduce drowning incidence attributed to the CSR.